Ligand-induced overexpression of a constitutively active β(2)-adrenergic receptor: Pharmacological creation of a phenotype in transgenic mice - Samama, Philippe (The National Academy of Sciences of the USA, 1997)
Transgenic overexpression (40- to 100-fold) of the wild-type human β(2)-adrenergic receptor in the hearts of mice leads to a marked increase in cardiac contractility, which is apparently due to the low level of spontaneous (i.e., agonist-independent) activity inherent in the receptor. Here we report that transgenic mice expressing a mutated constitutively active form of the receptor (CAM) show no such phenotype, owing to its modest expression (3-fold above endogenous cardiac β-adrenergic receptor levels). Surprisingly, treatment of the animals with a variety of β-adrenergic receptor ligands leads to a 50-fold increase in CAM β(2)-adrenergic receptor expression, by stabilizing the CAM β(2)-adrenergic receptor protein. Receptor up-regulation leads in turn to marked increases in adenylate cyclase activity, atrial tension determined in vitro, and indices of cardiac contractility determined in vivo. These results illustrate a novel mechanism for regulating physiological responses, i.e., ligand-induced stabilization of a constitutively active but inherently unstable protein.